Integrative personality assessment in wild Assamese macaques (Macaca assamensis) - Ebenau, Anja; von Borell, Christoph; Penke, Lars; Ostner, Julia; Schülke, Oliver (Journal of comparative psychology (Washington, D.C. : 1983), 2020)
In nonhuman animals, individuals of the same sex and age differ in their behavior patterns consistently across time, comparable with human personality differences. To draw conclusions about the adaptive value of behavior traits, it is essential to study them in the wild where animals are subject to the ecological pressures that promoted the evolution of behavior strategies. This study was conducted in the Phu Khieo Wildlife Sanctuary, Thailand, on 4 groups of habituated wild Assamese macaques by observers who had familiarized themselves with the subjects over the course of an ongoing long-term study. We used a multimethod approach enabling the most comprehensive understanding of variation in stable interindividual differences in a species-typical ecological setting. We combined trait ratings (TRs), assessed with observer-report questionnaires (54-item Hominoid Personality Questionnaire) of 107 individuals of diverse age-sex classes, with behavior codings (BCs) of 24 adult males. We found male and female personality constructs to be congruent and examined reliability and construct validity. Combining trait rating and behavioral coding, we found two solutions with five factors to best describe the personality structure of the males: one structure comprised the dimensions Gregariousness , Aggressiveness , Sociability and Vigilance , complemented by a Confidence domain and the other structure Opportunism , Confidence , Friendliness , Activity complemented with Vigiance . We discuss our findings with regard to the importance of construct validity and reproducibility in the context of method development and standardization in nonhuman animal personality research. (PsycINFO Database Record (c) 2020 APA, all rights reserved).